The impact of low interest rates on the insurance companies’ portfolio composition in EU countries - Stevan Luković; Miloš Pjanić; Božidar Čakajac; Mirela Mitrašević (Anali Ekonomskog fakulteta u Subotici, 2023)
The paper deals with the impact of low interest rate environment on the insurance companies’ portfolio composition in EU countries. The aim of the research is to show that continuously low interest rates could  influence insurance companies to become more exposed to risky asset classes, but there is also possibility that insurance companies remain mainly exposed to fixed income assets. The secondary data analysis is carried out to further examine the potential portfolio dynamics in Q4 2017-Q4 2021 period. The results of the analysis show that in most EU countries insurance companies remain invested in fixed-income assets. However, in eight countries (mostly Nordic countries) insurance companies have become significantly more exposed to equity and equity mutual funds, which suggests that portfolio reshaping has taken place in these countries.